2019
DOI: 10.1016/j.ebiom.2019.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the complex interplay between microbiota, HPV, inflammation and cancer through cervicovaginal metabolic profiling

Abstract: Background Dysbiotic vaginal microbiota have been implicated as contributors to persistent HPV-mediated cervical carcinogenesis and genital inflammation with mechanisms unknown. Given that cancer is a metabolic disease, metabolic profiling of the cervicovaginal microenvironment has the potential to reveal the functional interplay between the host and microbes in HPV persistence and progression to cancer. Methods Our study design included HPV-negative/positive controls, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
219
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 181 publications
(230 citation statements)
references
References 79 publications
11
219
0
Order By: Relevance
“…Consistent with the recent study of the urinary metabolome of women varying in HPV status published by Godoy‐Vitorino et al , we also observed higher levels of the central nervous system neuromodulator 4‐hydroxybutyric acid (aka gamma‐ hydroxybutyric acid or GHB), a precursor of GABA, in HPV + women. Consistent with the recent study by Ilhan et al , we also observed higher levels of several lyso‐ and monoacylglycerol‐lipids in HPV + women, including choline phosphate, and glycerophosphorylcholine. Within CST IV, HPV + women had lower levels of glutathione‐related metabolites including oxidised glutathione and reduced glutathione.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Consistent with the recent study of the urinary metabolome of women varying in HPV status published by Godoy‐Vitorino et al , we also observed higher levels of the central nervous system neuromodulator 4‐hydroxybutyric acid (aka gamma‐ hydroxybutyric acid or GHB), a precursor of GABA, in HPV + women. Consistent with the recent study by Ilhan et al , we also observed higher levels of several lyso‐ and monoacylglycerol‐lipids in HPV + women, including choline phosphate, and glycerophosphorylcholine. Within CST IV, HPV + women had lower levels of glutathione‐related metabolites including oxidised glutathione and reduced glutathione.…”
Section: Discussionsupporting
confidence: 92%
“…More recently, Ilhan et al . observed an association in the vaginal metabolome between lipids and cervical cancer. However, the impact of HPV infection remains relatively unexplored.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations